Associação entre estágios de mudança de comportamento, motivação e autoconceito em adultos praticantes de exercício físico - Silveira, Juliana Miyaki da (2010)
This study investigated the association between stages of behavior change, motivation and self-concept in practitioners of exercise. Study participants were 434 practitioners of exercise of the gyms affiliated to the NUSA (Sector Core of Gyms and Swimming Schools of Maringa) of both genders, aged 25 to 50 years. The instruments used were the Questionnaire of Regulating of Conduct on Exercise (BREQ-2), Algorithm of the Transtheoretical Model and Self-Concept Factor Scale. Data collection was performed individually in gyms and swimming schools. The Shapiro-Wilk, Mann Whitney and Chi-Square test were used for data analysis. The results showed significant differences in the comparison of the stages of motivation and self-concept regarding the gender. It was found that there were statistically significant difference in relation to introjected regulation and gender (p = 0,0001), in which female behavior is influenced by internal and external pressures; comparison between gender and self-concept showed significant difference between the self moral ethical dimension, somatic and self-control factor for women; the significant associations between stages of behavior change were found related to the practice time (over 6 months) stages of motivation (intrinsic motivation) and self-concept (self-control, moral ethical). It was concluded that there was association between stage of behavior change, motivation and self-concept with the understanding that to keep the desired/active behavior it is necessary the gradual and continuous construction in such behavior, considering the intrinsic motivation and change processes to provide individual experiences and in the environment directed to behavior changes.